2016
DOI: 10.5455/ijmsph.2016.20102015145
|View full text |Cite
|
Sign up to set email alerts
|

A study of prevalence and impact of dysmenorrhea and its associated symptoms among adolescent girls residing in slum areas of Vadodara city, Gujarat

Abstract: Background: Almost a quarter of India's population comprises of girls below 20 years and dysmenorrhea is a common problem among them. The magnitude of this problem is not clearly known in India. Objective:To estimate the prevalence and impact of dysmenorrhea and its associated symptoms among adolescent girls residing in slum areas of Vadodara city, Gujarat. Materials and Methods:A cross-sectional study, a part of field training of third-year medical students where adolescent girls (14-19 years) who experienced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 11 publications
1
12
2
Order By: Relevance
“…This is in congruence with some other previous Studies (Samir et al 2015;Khodakarami et al 2015;Thapa and Shrestha 2015. Various studies including Kulkarni and Durga (2011); Kumbhar et al (2011); Chauhan and Kodnani (2016) conducted among the slum adolescent girls and also the present study deciphered the high prevalence of dysmenorrhoea and PMS, and its association with BMI. Similar observation was also reported by among the adolescent girls residing in a slum area of western Maharashtra where a significant association has been found between BMI and both of the menstrual disorders.…”
Section: Discussionsupporting
confidence: 67%
“…This is in congruence with some other previous Studies (Samir et al 2015;Khodakarami et al 2015;Thapa and Shrestha 2015. Various studies including Kulkarni and Durga (2011); Kumbhar et al (2011); Chauhan and Kodnani (2016) conducted among the slum adolescent girls and also the present study deciphered the high prevalence of dysmenorrhoea and PMS, and its association with BMI. Similar observation was also reported by among the adolescent girls residing in a slum area of western Maharashtra where a significant association has been found between BMI and both of the menstrual disorders.…”
Section: Discussionsupporting
confidence: 67%
“…In some countries such as Turkey (72.7%) (41), India (75%) (42) and Malaysia (74.5%) (43), the prevalence has been reported similar, but in other countries they are different; such as 80% in Australia (44) and Hong Kong (5), approximately 64% in Togo (45), 61% in Saudi Arabia (46) The definition of dysmenorrhea and scales used to determine it, changed the prevalence rate. Without considering the severity of pain, interfering with daily activities, requiring analgesic drugs or absenteeism of school or work, the definition of dysmenorrhea is the presence of pain during menstruation.…”
Section: Discussionmentioning
confidence: 99%
“…The logistic regression analysis showed that the rate of dysmenorrhoea was twice as high for those who had a family history of dysmenorrhoea than for those who did not. Many other studies have also indicated that family history of dysmenorrhoea is an important risk factor (Chauhan & Kodnani, ; Faramarzi & Salmalian, ; Gagua, Tkeshelashvili, & Gagua, ; Ju, Jones, & Mishra, ; Kural, Noor, Pandit, Joshi, & Patil, ; Ozerdogan et al, ; Pejĉić & Janković, ; Tavallaee et al, ; Unsal et al, ). While some researchers think that this finding indicates that dysmenorrhoea is a behaviour learned from mothers or sisters (Faramarzi & Salmalian, ; Kural et al, ; Pejĉić & Janković, ), others argue for a genetic predisposition for dysmenorrhoea (Wu et al, ).…”
Section: Discussionmentioning
confidence: 97%
“…Rodrigues et al () found that as pain severity increases, the ability to affect daily life also increases. Previous studies have shown that dysmenorrhoea causes class absences (Chauhan & Kodnani, ; Coşkuner Potur & Kömürcü, ; Ortiz et al, ), as well as limited daily activities (Chauhan & Kodnani, ; Ortiz et al, ) and social relationships (Chauhan & Kodnani, ; Coşkuner Potur & Kömürcü, ). These findings indicate that students should use effective methods to manage and treat dysmenorrhoea.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation